2020
DOI: 10.1371/journal.pone.0233698
|View full text |Cite
|
Sign up to set email alerts
|

The 4 youth by youth HIV self-testing crowdsourcing contest: A qualitative evaluation

Abstract: IntroductionCrowdsourcing, a participatory approach to solicit ideas from a large group of diverse individuals, provides an opportunity to nurture youth participation in HIV self-testing service design. The objective of this study was to describe the responses to a crowdsourcing contest aimed at soliciting ideas on how to promote HIV self-testing (HIVST) among young people in Nigeria. MethodsThe "4 Youth by Youth" HIV Self-Testing Crowdsourcing contest was an online and off-line contest that asked Nigerian you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 39 publications
1
67
1
Order By: Relevance
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
“…Both studies were conducted after 2010. We also assessed of the extent of youth engagement over time by comparing engagement in studies conducted in or before 2010 [19,20,22,23,25‐27,31,33,34,39‐41,45‐48,52‐54,59,60,66,68,72,73,77,78,80,82,83,88,89,109,115,121,130], to studies conducted after 2010 [21,24,28‐30,32,35‐37,42‐44,50,51,56‐58,60,62‐64,67,69‐71,75,76,79,81,84‐86,90,100,110,111,129]. We found youth engagement in 28 out of 37 interventions (76%) conducted in or before 2010, and in 30 out of 37 interventions (81%) conducted after 2010.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global efforts and collaborations between WHO, researchers, local health agencies, donors, and policy makers have addressed some of these limitations. Initiatives such as but not limited to the Self- T esting A f R ica (STAR), the largest HIVST implementation science project to date ( 44 ), 4 Youth by Youth crowdsourced HIVST interventions ( 45 , 46 ), and S elf- T esting E ducation and P romotion (STEP) project ( 28 , 33 ), have created a market for HIVST in sub-Saharan Africa. These initiatives combined with other studies around the globe have accelerated access to HIVST by gathering the necessary acceptability, feasibility, and fidelity data, creating an enabling environment with regards to HIVST policies, generating diverse demand through multiple distribution channels, and creating advocacy for additional financing, as well as accelerate market entry for suppliers at affordable and sustainable prices ( 44 , 45 , 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives such as but not limited to the Self- T esting A f R ica (STAR), the largest HIVST implementation science project to date ( 44 ), 4 Youth by Youth crowdsourced HIVST interventions ( 45 , 46 ), and S elf- T esting E ducation and P romotion (STEP) project ( 28 , 33 ), have created a market for HIVST in sub-Saharan Africa. These initiatives combined with other studies around the globe have accelerated access to HIVST by gathering the necessary acceptability, feasibility, and fidelity data, creating an enabling environment with regards to HIVST policies, generating diverse demand through multiple distribution channels, and creating advocacy for additional financing, as well as accelerate market entry for suppliers at affordable and sustainable prices ( 44 , 45 , 47 49 ). Similar initiatives are needed swiftly to gather additional accuracy, acceptability, feasibility, and programmatic data to encourage policy makers, donors, and local health agencies to support for SARS-CoV-2ST implementation and scale up.…”
Section: Discussionmentioning
confidence: 99%